Зовнішньополітична діяльність Білоруської Народної Республіки у 1918−1925 рр. - Panasyuk, Оleksandr; Панасюк, Олександр (Східноєвропейський національний університет ім. Лесі Українки, 2013)
У статті здійснено спробу проаналізувати основні напрями зовнішньої політики Білоруської Народної Республіки у 1918–1925 рр. Визначено основні форми й методи ведення дипломатії БНР, розглянуто основні варіанти вирішення «білоруського питання» в системі міжнародних відносин, причини невдач зовнішньої політики.The article considers and analyzer the main trends in foreign policy of the National Republic of Belarus in 1918-1925 years. It was pointed out main forms and methods of diplomacy of the National Republic of Belarus. It is noted that the establishment of diplomatic relations was an important and challenging task for Belarusian authorities. The complexity was the uncertainty of the legal status of the state. It was regarded the main variants of the solution of «The Belarusians question» in the system of international relations.
Foreign Political Relations of the National Republic of Belarus in 1928−1925 Years.
Keywords: Білоруська Народна Республіка; зовнішньополітичні відносини; Всебілоруський з’їзд; Статутна грамота; Народний секретаріат; Народна рада; Й. Воронко; А. Луцкевич; the National Republic of Belarus; foreign policy relations; Belarusian congress; Charter; People’s Secretariat; I. Voronko; A. Lutskevich